THEORETICAL MULTIPLE ANALYSIS OF EXTREMAL RESULTS PHENOMENOLOGY LIES - A. Tarasov (Вестник университета)
This article discusses the results of theoretical and empirical research of the phenomena of false information using copyright questionnaire FPL. An attempt was made to theoretical analysis of multiple extremal results phenomenology lies. It is shown that the individual differences of Phenomenology in the process of communication lie demonstrate extreme (extreme) results of test subjects on questionnaire scales FPL. There is also the regularity of unmonotonous similarities and differences of the extreme ratios of Phenomenology lies at the level of results on individual scales FPL in extreme groups of examinees.